Assessment of knowledge and skill of health care providers in management of child abuse in different level hospital in Bangladesh - Khanam, Rawshan Ara; Begum, Kohinoor; Halim, Abdul; Najneen, Khadiza (Journal of Shaheed Suhrawardy Medical College, 2012)
Challenges to the health of our children have been changing in recent decades as we have taken control over different diseases through immunization and child health program . But newer problems are uncovered. Child Abuse and Neglect is one of them . World community has given emphasis on this very old but unnoticed problem ,this problem is received very less emphasis in South East Asia. With the objectives -to assess the knowledge and skill of working doctors and nurses of concern department in managing child abuse and to help the service providers to improve their knowledge and skill to deal with child abuse and to identify the laps and gaps in the area where abused children are dealt with, this study was carried out in two Medical College Hospitals, two District Hospitals and two Upazilla Health Complexes from November 2005 to July 2006. Selected departments for study were - Obstetrics & Gynaecology, Paediatrics, Orthopaedics. Burn, Casualty, Psychiatry and OCC, (DMCH) in Medical College level; Obstetrics & Gynaecology, Paediatrics, Surgery in district level and all from Upazilla level. Working doctors of all level and senior staff nurses were included in this study. Assessment of knowledge and skill was done before and after intervention by observation and face to face interview by using a pre tested prepared questionairre .Laps and gaps were identified by observation and interview. Intervention was given by a one day workshop in each level of hospital . About 155 care providers participated in pre and post intervention interview . Of them- 109 were doctor and 46 were nurses. Among them 71 (Doc. 55 + Nurse 16) from two Medical College Hospitals, 42 (Doc. 33 + Nurse 9) from two District Hospitals & 42 (Doc. 21 + Nurse 21) from 2 Upazilla Health Complexes . It was surprising that only 11 % health care provides correctly knows that who are the children , only 10 % providers knows about the different types of abuse and only 15 % providers believe that they have sufficient knowledge to manage an abused child. Knowledge level is much higher among the doctors working in teaching hospitals and poorest in UHC. Nurses are less knowledgeable than doctors . Score of nurses is more or less similar in all level of hospitals. The pre and post intervention changes were analyzed by using unpaired student's t test and p value was significant .On job training of care providers on management of abused child is very important and inclusion of this issue in medical and nursing curricula is necessary. DOI: http://dx.doi.org/10.3329/jssmc.v1i1.12166 Journal of Shaheed Suhrawardy Medical College Vol.1, No.1, December 2009 p.2-5